MODELING THE FUNCTIONALITIES OF AN AUTOMATED SYSTEM FOR MANAGING MOVEMENT IN THE AIR - Abdullayev, Sanjar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Automated Traffic Control (ATC) systems are crucial in today's global aviation. This research employed mathematical approaches to model the functionalities of ATC systems. Using the created model, algorithms were developed to ensure the safe and efficient movement of aircraft. The research results were presented graphically and in tables, demonstrating an increase in system efficiency.